The Factors Related to Hypertension in the Elderly in Simataniari Health Center, Angkola Sangkunur District in 2018 - Ramadhini, Delfi; Siregar, Yenni Farida; ., Salnisah (Jurnal Kesehatan Ilmiah Aufa Royhan, 2019)
Hypertension or high blood pressure is a disorder in the blood vessels that causes the supply of oxygen and nutrients carried by the blood to be blocked to the body's tissues that need it. The prevalence of hypertension in the world according to WHO in 2017, 1 billion people in the world suffer from hyperlension, two-thirds of whom are in developing countries with low to moderate incomes. This research is an analytic study with a descriptive approach. This type of research design is cross-sectional. The population in this study is all the elderly in the Simataniari Health Center with a total sample of 76 elderly. Data were analyzed univariately and bivariately using the Chi-square test α = 95%. The results showed the majority of the elderly have hypertension, the majority there is a genetic history, the majority of women and the majority with more nutritional status, and there is a relationship between genetic history and nutritional status with hypertension in the elderly, while there is no gender relationship with hypertension in the elderly. It is expected that the elderly carry out routine blood pressure checks at least 2 times a week and pay attention to genetic and maintain nutritional status.